Exploring Foreign Direct Investment (FDI) Flow and Economic Growth: A Systematic Approach - Abdullahi Sule, Sani; Rimi, Saadatu (International Journal on Economics, Finance and Sustainable Development (IJEFSD), 2025)
This research aims to deepen the understanding of Foreign Direct Investment (FDI) and its relationship with economic growth by systematically reviewing existing literature. The study also seeks to elucidate the factors influencing FDI and how FDI flows impact economic growth, alongside examining the opportunities and challenges posed by FDI adoption. This study conducted a review of 100 publications published between 2001 and 2022 using data sourced from the Scopus database, as well as other comprehensive databases such as ScienceDirect, Emerald Insight, JStor, PLOS ONE, Springer, and Taylor & Francis. The review incorporated empirical research, case studies, and reports from institutions like the World Bank and OECD. Additionally, related books and theoretical frameworks were referenced to support the analysis. The literature indicates that FDI can influence economic growth in various ways. Broadly, FDI is recognized as a significant driver of development and an essential part of an open and efficient international economic system. However, the distribution of FDI benefits is not uniform or automatic across countries, sectors, or local communities. The findings highlight that social and macroeconomic factors play crucial roles in shaping business decisions regarding FDI, contingent on the unique characteristics of the host country. This research provides a conceptual framework based on existing literature for understanding the impact of FDI on economic growth. It encourages empirical studies to validate and test the applicability and effectiveness of this framework in real-world contexts. Originality/value by synthesizing diverse perspectives from the literature, this paper identifies key factors influencing FDI flows and their impact on economic growth. It offers practical insights that could assist investors in comprehending FDI dynamics and their implications for economic development.